Tunisian Maturity-Onset Diabetes of the Young: A Short Review and a New Molecular and Clinical Investigation - Moalla, Mariam; Safi, Wajdi; Babiker Mansour, Maab; Hadj Kacem, Mohamed; Mahfood, Mona; Abid, Mohamed; Kammoun, Thouraya; Hachicha, Mongia; Mnif-Feki, Mouna; Hadj Kacem, Faten; Hadj Kacem, Hassen (Frontiers in Endocrinology, 2021)
Introduction/Aims: Maturity-Onset Diabetes of the Young (MODY) is monogenic non-autoimmune diabetes with 14 different genetic forms. MODY-related mutations are rarely found in the Tunisian population. Here, we explored MODY-related gene sequences among seventeen unrelated Tunisian probands qualifying the MODY clinical criteria. Materials and Methods: The GCK and HNF1A genes were systematically analyzed by direct sequencing in all probands. Then, clinical exome sequencing of 4813 genes was performed on three unrelated patients. Among them, one hundred thirty-three genes have been reported to be involved in the regulation of glucose metabolism, β-cell development, differentiation, and function. All identified variants were analyzed according to their frequencies in the GnomAD database and validated by direct sequencing. Results: We identified the previously reported GCK mutation (rs1085307455) in one patient. The clinical features of the MODY2 proband were similar to previous reports. In this study, we revealed rare and novel alterations in GCK (rs780806456) and ABCC8 (rs201499958) genes with uncertain significance. We also found two likely benign alterations in HNF1A (rs1800574) and KLF11 (rs35927125) genes with minor allele frequencies similar to those depicted in public databases. No pathogenic variants have been identified through clinical exome analysis. Conclusions: The most appropriate patients were selected, following a strict clinical screening approach, for genetic testing. However, the known MODY1-13 genes could not explain most of the Tunisian MODY cases, suggesting the involvement of unidentified genes in the majority of Tunisian affected families.